Mount St. Helens, the1980 Re-awakening and Continuing Seismic Activity - Malone, Stephen (Geoscience Canada, 1990)
Summary Mount St. Helens has been seismically monitored since the summer of 1972. Seismic activity recorded during the 1970s by a single station located on the west flank of the volcano was limited to small swarms of high-frequency earthquakes and low-frequency transient signals usually attributed to glacier motion. The first seismic activity that was recognized as being unusual and with possible volcanic significance was a magnitude 4.2 earthquake on the afternoon of March 20, 1980. In retrospect, the initial unusual seismic activity began several days earlier as small, low-frequency earthquakes with seismogram character similar to, but not exactly the same as, the glacier events. Following the March 20 event, earthquake activity rapidly increased over the next five days untilon March 26 as many as eight magnitude 4+ earthquakes per hour were occurring. Onthe next day, phreatic eruptions began. From then until the climactic eruption on May 18, seismic energy release rates remained fairly constant though the number of earthquakes per unit time decreased. During this period, intermittent phreatic eruptions took place as well as continuous deformation of the northflank. The earthquakes were located in a limited volume directly under the volcano at shallow depths and now are interpreted to have been caused by the fracturing and faulting of shallow volcanic rocks as magma was injected into the base of the volcano. The major eruption on May 16 was triggered byone of these earthquakes, which caused aslope failure of the north flank. As this eruption progressed, shallow earthquake activity declined and deeper activity began. These deeper earthquakes outline the magma conduit system indicating the presence of a small crustal magma reservoir at a depth of 7to 12 km. Shallow seismicity preceding subsequent eruptions provided data to help with the prediction of most of these eruptions. Deeper seismicity has not been as obviously related to individual eruptions. We speculate that it reflects adjustments in the magma chamber and conduit system, due, in different cases, to a reduction or increase in magma pressure.